Adjunctive use of fluoride rinsing and brush-on gel increased incipient caries-like lesion remineralization compared with fluoride toothpaste alone in situ. (18th August 2019) - Bhongsatiern, Phan; Manovilas, Ploypailin; Songvejkasem, Methaphon; Songsiripradubboon, Siriporn; Tharapiwattananon, Thipawan; Techalertpaisarn, Paiboon; Hamba, Hidenori; Tagami, Junji; Birkhed, Dowen; Trairatvorakul, Chutima
Abstract: Objective: The objective of this study was to compare the remineralizing effect of sodium fluoride (NaF) mouth rinse or NaF gel as an adjunct to NaF dentifrice on incipient caries-like lesions in an in situ cross-over design study, with three sessions of 30 days each. Materials and methods: Orthodontic brackets with artificial demineralized enamel slabs were attached to the upper first molars of 12 participants. A set of 3 test specimens from the same tooth was randomly assigned to each participant and allocated into three 30-day sessions: 1) brushing with 0.22% NaF dentifrice 2 times/day (F dentifrice), 2) brushing with 0.22% NaF dentifrice 2 times/day+ rinsing with 0.05% NaF before bedtime (F mouth rinse), 3) brushing with 0.22% NaF dentifrice 2 times/day + brushing with 1.1% NaF gel before bedtime (F brush-on gel). The mineral gain and lesion depth of the specimens were evaluated by micro-computed tomography. Results: The mean mineral gain from the NaF mouth rinse and the NaF brush-on gel was similar, but greater than that from the NaF dentifrice ( p < .05). The NaF brush-on gel yielded the greatest mean depth of remineralization (168 µm), followed by the NaF mouth rinse (144 µm). Both depths were significantly greater than that of the NaF dentifrice (84 µm) ( p < .05). Conclusions: Both 0.05% NaF mouth rinse and 1.1% NaF brush-on gel, used at bedtime, increased incipient caries-like lesion remineralization in situ in combination with brushing with NaF dentifrice twice a day.